Management of Long QT Syndrome in Women Before, During, and After Pregnancy - Caroline Taylor; Bruce S Stambler (US Cardiology Review)
Congenital long QT syndrome (LQTS) is a primary genetic and electrical disorder that increases risk for torsades de pointes, syncope, and sudden death. Post-pubertal women with LQTS require specialized multidisciplinary management before, during, and after pregnancy involving cardiology and obstetrics to reduce risk for cardiac events in themselves and their fetuses and babies. The risk of potentially life-threatening events is lower during pregnancy but increases significantly during the 9-month postpartum period. Treatment of women with LQTS with a preferred β-blocker at optimal doses along with close monitoring are indicated throughout pregnancy and during the high-risk postpartum period.